Pelaksanaan dan Hambatan dalam Pemberian Remisi terhadap Warga Binaan di Lembaga Pemasyarakatan Kelas II A Kupang - Aditya Joshua Panggalaha; Rudepel Petrus Leo; Darius A Kian (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
The purpose of this study is to analyze the implementation and obstacles in granting remission to prisoners in Class II A Kupang Correctional Institution. This research is empirical juridical research, which is a type of sociological legal research that examines the applicable legal provisions and has occurred in community life with the type of data used is primary data obtained through interviews and documentation, and secondary data that provides information and is complementary to the primary. The data is analyzed descriptively-qualitatively. The research was conducted at Class II A Kupang Correctional Institution. Based on the results of the study, it can be concluded that the implementation of the granting of remission at the Class II A Kupang Correctional Institution is that Remission is a reduction in the period of serving a sentence given to prisoners and children in conflict with the law (children) who meet the requirements in the legislation. The obstacles faced by Kupang Class II A Correctional Institution in the implementation of remission are administrative factors, institutional factors, facilities and infrastructure factors.